Primary fallopian tube carcinoma: Clinicopathological analysis of 12 cases - Yu-Che Ou; Hsiu-Yu Huang; Chao-Cheng Huang; Chan-Chao ChangChien; Chih-Wen Tseng; Hao Lin (Elsevier, 2011)
Objective: Primary fallopian tube carcinoma is one of the least common gynecological cancers and is difficult to diagnose preoperatively. We aimed to analyze the clinicopathological characteristics of this rare disease and to identify the prognostic factors predicting prognosis. Materials and Methods: Twelve cases of primary fallopian tube carcinoma that had been diagnosed and treated in Kaohsiung Chang Gung Memorial Hospital between July 1986 and December 2005 were retrospectively reviewed. Factors, including age, gravidity, parity, stage, surgical intervention, pathological findings, relapse, and survival, were analyzed. Results: The median age of the 12 cases was 54 years (range, 32-67 years), whereas the median follow-up time was 38 months. None of the 12 cases were diagnosed preoperatively. Preoperative diagnoses were adnexal mass of unknown nature in six (50%), tubo-ovarian abscess in three (25%), ovarian carcinoma in two (16.7%), and endometrioma in one (8.3%) cases. Two patients (16.7%) had experienced the typical symptom of watery vaginal discharge. Three patients (25%) were in Stage I, three (25%) in Stage II, four (33.3%) in Stage III, and two (16.7%) were unstaged. Nine patients had received postoperative platinum-based adjuvant chemotherapy. The 5-year disease-free survival rate was 64%. On evaluating the correlation between clinicopathological parameters and survival, only the Federation of Gynecology and Obstetrics stage (p=0.017) was a significant prognostic factor. Conclusion: Although preoperative diagnosis of fallopian tube carcinoma is difficult, still 16.7% of our patients experienced the typical symptom suggestive of tubal carcinoma. Prognostic factors associated with fallopian tube cancer were similar to those of epithelial ovarian cancer.